2017
DOI: 10.3892/mmr.2017.7259
|View full text |Cite
|
Sign up to set email alerts
|

Emodin alleviates severe acute pancreatitis-associated acute lung injury by decreasing pre-B-cell colony-enhancing factor expression and promoting polymorphonuclear neutrophil apoptosis

Abstract: The present study aimed to evaluate the protective effects of emodin on severe acute pancreatitis (SAP)-associated acute lung injury (ALI), and investigated the possible mechanism involved. SAP was induced in Sprague-Dawley rats by retrograde infusion of 5% sodium taurocholate (1 ml/kg), after which, rats were divided into various groups and were administered emodin, FK866 [a competitive inhibitor of pre-B-cell colony-enhancing factor (PBEF)] or dexamethasone (DEX). DEX was used as a positive control. Subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 43 publications
0
36
0
1
Order By: Relevance
“…Studies have demonstrated that emodin is a potential candidate in the treatment of AP-associated lung injury, 31,32 but the underlying mechanisms by which emodin performs its pharmacological activities remain incompletely known. The present study investigated the effect of emodin on Nrf2/ NLRP3 signaling pathway in AP-associated lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that emodin is a potential candidate in the treatment of AP-associated lung injury, 31,32 but the underlying mechanisms by which emodin performs its pharmacological activities remain incompletely known. The present study investigated the effect of emodin on Nrf2/ NLRP3 signaling pathway in AP-associated lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…SAP is a life-threatening situation caused by multiple organ dysfunctions (MODS), which is induced by inflammation cascade activation. The mortality rate associates with SAP is much higher than that of AP, which was reported at 15–30% [ 2 ]. The mechanisms of SAP are still not fully understood and no agent with satisfied efficacy has been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Sepsis is the primary etiology of ALI ( 3 ) and a common admission to the intensive care unit ( 4 ); it induces pulmonary inflammation leading to disruption of endothelial–epithelial barriers by surge release of pro-inflammatory cytokines, which in turn increase the permeability of the alveolar-capillary membrane, pulmonary infiltration, and edema ( 5 , 6 ). Other causes of ALI include trauma ( 7 ), aspiration ( 8 ), acute pancreatitis ( 9 ), drug toxicity ( 10 ), etc. Ultimately, gas exchange across the alveolar-capillary membrane becomes severely impaired and acute respiratory failure and hypoxia occur ( 11 ).…”
Section: Introductionmentioning
confidence: 99%